2021
DOI: 10.1002/ppul.25439
|View full text |Cite
|
Sign up to set email alerts
|

The starting rate for high‐flow nasal cannula oxygen therapy in infants with bronchiolitis: Is clinical judgment enough?

Abstract: Objectives: To determine whether in infants with bronchiolitis admitted to a pediatric intensive care unit (PICU) the starting rate for high-flow nasal cannula (HFNC) therapy set by the attending physicians upon clinical judgment meets patients' peak inspiratory flow (PIF) demands and how it influences respiratory mechanics and breathing effort.Methodology: We simultaneously obtained respiratory flow and esophageal pressure data from 31 young infants with moderate-to-severe bronchiolitis before and after setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Consequently, 44 studies were included: 15 were in vitro studies [ 12 26 ], two combined in vitro and in vivo studies were conducted on neonates [ 27 , 28 ] and 27 were clinical studies [ 6 8 , 29 52 ]. In the clinical studies ( supplementary table S1 ), 14 were conducted on neonates [ 29 41 , 51 ] including preterm infants with [ 29 , 31 , 34 , 35 , 37 , 38 , 51 ] or without [ 30 , 32 , 33 , 36 , 39 41 ] lung disease, while 13 focused on paediatric patients with bronchiolitis [ 6 8 , 44 , 46 48 , 50 , 52 ] or requiring HFNC for various reasons [ 42 , 43 , 45 , 49 ], with most the patients younger than 2 years. Four of these studies were RCTs [ 48 51 ], and ten were randomised crossover studies [ 31 , 33 , 34 , 37 , 39 41 , 43 , 45 , 46 ].…”
Section: Literature Search Strategy and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, 44 studies were included: 15 were in vitro studies [ 12 26 ], two combined in vitro and in vivo studies were conducted on neonates [ 27 , 28 ] and 27 were clinical studies [ 6 8 , 29 52 ]. In the clinical studies ( supplementary table S1 ), 14 were conducted on neonates [ 29 41 , 51 ] including preterm infants with [ 29 , 31 , 34 , 35 , 37 , 38 , 51 ] or without [ 30 , 32 , 33 , 36 , 39 41 ] lung disease, while 13 focused on paediatric patients with bronchiolitis [ 6 8 , 44 , 46 48 , 50 , 52 ] or requiring HFNC for various reasons [ 42 , 43 , 45 , 49 ], with most the patients younger than 2 years. Four of these studies were RCTs [ 48 51 ], and ten were randomised crossover studies [ 31 , 33 , 34 , 37 , 39 41 , 43 , 45 , 46 ].…”
Section: Literature Search Strategy and Resultsmentioning
confidence: 99%
“…In the two studies involving infants with bronchiolitis, an increase in flow was associated with an improvement in the patient's S pO 2 / F IO 2 ratio ( supplementary table S4 ) [ 7 , 8 ]. When the flow was increased from 0.5 to 2 L·kg −1 ·min −1 [ 44 , 46 ], no significant differences were observed in V T and minute ventilation, as assessed by respiratory inductance plethysmography [ 45 ], pneumotachography [ 44 ] or electric impedance tomography [ 46 ]. Moreover, when flow was increased from 0.4 to 2 L·kg −1 ·min −1 , a reduction in respiratory rate was observed in six studies ( figure 3a ) [ 6 , 8 , 43 46 ], except for the study conducted by N ascimento et al [ 7 ], in which no significant differences in respiratory rate were observed across flows of 0.5–2 L·kg −1 ·min −1 when using the Vapotherm device.…”
Section: The Effects Of Different Flow Settings In Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to several studies cautioning providers about the questionable impact of higher flow rates, suggesting prolonged weaning. 27,28 Higher initial maximum flow rates fit with observational and physiological studies that suggest HFNC flow rates approximating 2 L/kg/min may be necessary to unload respiratory muscles, improve work of breathing, or generate positive airway pressure in children with bronchiolitis [29][30][31][32][33][34] and several studies of protocols with higher flow rates have demonstrated some favorable outcomes. 22,24 Our findings also support practice standardization and weaning guidance for mitigating prolonged HFNC duration.…”
Section: F I G U R E 2 Heated High Flow Pathwaymentioning
confidence: 93%
“…It has been reported that an initial high-flow rate of nearly 2 L/kg/min meets patients' flow demands and improves respiratory mechanics and breathing effort [61]. A prospective, observational and analytical study showed that an initial flow of 15 L/min is associated with a faster improvement of respiratory rate and a lower treatment failure rate [62].…”
Section: Oxygen Therapymentioning
confidence: 99%